Reading and Writing the Qur'an (BTQ) as Compulsory Class Load for Elementary Schools - Suhartini; Siti Maulidah; M. Fathur Rohman (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This research focuses on implementing compulsory class load to improve the quality of reading and writing Qur'an, targeted at Sukodermo Purwosari Elementary School students in Pasuruan. The discussion method in this study uses a descriptive qualitative method approach. The problems faced by teachers of Islamic religious education in learning the local content curriculum for reading and writing the Qur'an can be divided into supporting factors and inhibiting factors. Supporting factors come from the students themselves as well as facilities and infrastructure. Factors that come from the students are the moral encouragement or enthusiasm in learning to read and write the Qur'an and facilities and infrastructure, like prayer rooms which are commonly used in religious learning or religious activities as is routinely carried out at SDN Sukodermo Purwosari Pasuruan, that is, reading short letters of Qur'an and Asmaul Husnah every morning before starting lessons and istighozah every Legi Friday. The inhibiting factors are also found in students, facilities, and infrastructure. The inhibiting factors that exist in students are the level of intelligence and the different psychology of students. The ability to learn to read and write the Qur'an is uneven. Even though almost 89% of students can already read and write the Qur'an well, And the need for more tools to support the process of learning to read and write the Qur'an.